2007
DOI: 10.1111/j.1469-7610.2007.01792.x
|View full text |Cite
|
Sign up to set email alerts
|

Early adolescent outcomes of institutionally deprived and non‐deprived adoptees. III. Quasi‐autism

Abstract: The findings at age 11/12 years confirmed the reality and clinical significance of the quasi-autistic patterns seen in over 1 in 10 of the children who experienced profound institutional deprivation. Although there were important similarities with 'ordinary' autism, the dissimilarities suggest a different meaning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(122 citation statements)
references
References 20 publications
(19 reference statements)
3
110
0
9
Order By: Relevance
“…Such higher risk for suicide is consistent with the identity disorders often observed in infant psychiatry in the case of adolescents internationally adopted in infancy [14]. What is also clear is that length of preadoption time and severity of caregiving deprivation emerge as two predicting factors of delays in the development of neurological and age-level motor skills, and that the simple enrichment of the adopted child's environment following adoption proves insufficient to repair such damage beyond certain critical ages or sensitive periods [10,[15][16][17][18]. These sensitive periods and cutoff ages differ depending on the institution and country of origin according to the severity of deprivation to which the child has been exposed [19].…”
Section: Introductionsupporting
confidence: 64%
“…Such higher risk for suicide is consistent with the identity disorders often observed in infant psychiatry in the case of adolescents internationally adopted in infancy [14]. What is also clear is that length of preadoption time and severity of caregiving deprivation emerge as two predicting factors of delays in the development of neurological and age-level motor skills, and that the simple enrichment of the adopted child's environment following adoption proves insufficient to repair such damage beyond certain critical ages or sensitive periods [10,[15][16][17][18]. These sensitive periods and cutoff ages differ depending on the institution and country of origin according to the severity of deprivation to which the child has been exposed [19].…”
Section: Introductionsupporting
confidence: 64%
“…Both children with autism [26,27] and children placed in institutional care at an early age [28] show deficiencies in face processing. In addition, both groups achieve below average scores on the theory of mind tasks [24], even when these scores are adjusted for the level of language development and non-verbal intelligence [29].…”
Section: Shared Characteristics Of Socially Deprived Subjects and Chimentioning
confidence: 92%
“…It is noteworthy that both institutionalized children and autistic patients have characteristics of abnormal connectivity between prefrontal and parietal regions [13,67] and between prefrontal and temporal regions [12,68], that perhaps are related with cognitive and behavioral similarities at school age (4-6 years). However, these similarities become less clear in the adolescence and hence only a small group of institutionalized adolescents have a permanent quasi-autistic pattern upon turning 11 years [65]. Also, the same EEG characteristics between prefrontal and temporal cortices have been found in schizophrenic patients during accepted and rejected proposals in execution of the Ultimatum Game [28].…”
Section: Eeg Correlationmentioning
confidence: 98%
“…Some authors have identified that institutionalized population has some quasi-autistic cognitive characteristics [64,65] since both institutionalized children and autistic patients have impaired social performance although the institutionalized group presents greater flexibility, greater social approach and an increased incidence of indiscriminate friendly compared to children diagnosed with autism [66]. It is noteworthy that both institutionalized children and autistic patients have characteristics of abnormal connectivity between prefrontal and parietal regions [13,67] and between prefrontal and temporal regions [12,68], that perhaps are related with cognitive and behavioral similarities at school age (4-6 years).…”
Section: Eeg Correlationmentioning
confidence: 99%